Mathematical Methods in Signal Processing and Digital Image Analysis - Dahlhaus, R. (Springer, 2017)
The aim of this volume is to bring together research directions in theoretical signal and imaging processing developed rather independently in electrical engineering, theoretical physics, mathematics and the computer sciences.